Comparing the effects of ipragliflozin versus metformin on visceral fat reduction and metabolic dysfunction in Japanese patients with type 2 diabetes treated with sitagliptin: A prospective, multicentre, open‐label, blinded‐endpoint, randomized controlled study (PRIME‐V study). Issue 8 (8th May 2019) - Koshizaka, Masaya; Ishikawa, Ko; Ishibashi, Ryoichi; Maezawa, Yoshiro; Sakamoto, Kenichi; Uchida, Daigaku; Nakamura, Susumu; Yamaga, Masaya; Yokoh, Hidetaka; Kobayashi, Akina; Onishi, Shunichiro; Kobayashi, Kazuki; et al.
Abstract: A prospective, multicentre, open‐label, blinded‐endpoint, randomized controlled study was conducted to evaluate the efficacy of treatment with ipragliflozin (sodium‐dependent glucose transporter‐2 inhibitor) versus metformin for visceral fat reduction and glycaemic control among Japanese patients with type 2 diabetes treated with sitagliptin, HbA1c levels of 7%‐10%, and body mass index (BMI) ≥ 22 kg/m 2 . Patients were randomly assigned (1:1) to receive ipragliflozin 50 mg or metformin 1000‐1500 mg daily. The primary outcome was change in visceral fat area as measured by computed tomography after 24 weeks of therapy. The secondary outcomes were effects on glucose metabolism and lipid metabolism. Mean percentage reduction in visceral fat area was significantly greater in the ipragliflozin group than in the metformin group (−12.06% vs. −3.65%, P = 0.040). Ipragliflozin also significantly reduced BMI, subcutaneous fat area, waist circumference, fasting insulin, and homeostatic model assessment (HOMA)‐resistance, and increased HDL‐cholesterol levels. Metformin significantly reduced HbA1c and LDL‐cholesterol levels and increased HOMA‐beta. There were no severe adverse events. The use of ipragliflozin or metformin in combination with dipeptidyl peptidase‐4 inhibitors, widely used in Japan, may have beneficial effects in ameliorating multiple cardiovascular risk factors.